Web design all-in-one for dummies - Jenkins, Sue, 1966- (--For dummies., 2009)
Book 1 covers planning, defining your target audience, choosing the right software, and more -- Book II acquaints you with HTML, CSS, and JavaScript, plus how to choose a layout and optimize graphics -- Book III gets down to nuts and bolts : putting text, images, hyperlinks, and multimedia files together, organizing content, and building navigation systems -- Book IV teaches you how to test and validate so everyone can enjoy your site -- Book V helps you get your site online and keep it current.